Vaginal Lubrication after Cervicovaginal Stimulation Is Facilitated by Phosphodiesterase Type 5 Inhibition in Ovariectomized Mice. (27th March 2013) - Gamé, Xavier; Roumiguié, Mathieu; Bouali, Ourdia; Allard, Julien; Gourdy, Pierre; Mazerolles, Catherine; Rischmann, Pascal; Arnal, Jean‐François; Malavaud, Bernard
Abstract Introduction Nitric oxide synthases (NOSs) and estrogen receptors are expressed in the vagina. Aim We aimed to assess the impact of sildenafil on vaginal lubrication according to the hormonal status and to determine the role of the neuronal isoform of NOS (nNOS). Methods Four‐week‐old C57/BL6 female mice were sham operated or ovariectomized. At 10 weeks of age, they were injected intraperitoneally by any combination of sildenafil, 7‐nitroindazole (7‐NI)—a potent selective nNOS inhibitor—or the corresponding vehicles. Vaginal lubrication was induced in a physiological manner by cervical vaginal probing and quantified depending on the hormonal and pharmacological conditions. The animals were then sacrificed for vaginal histomorphometry. Main Outcome Measures The main outcome measure is the quantification of vaginal transudate after cervicovaginal stimulation and vaginal histomorphometry. Results Sildenafil increased cervicovaginal probing‐induced vaginal lubrication in ovariectomized and sham‐operated animals. Ovariectomized mice exhibited decreased vaginal lubrication as compared with sham‐operated mice. When taking into account the presence of severe vaginal atrophy, a threefold increase in transudate per gram of vagina wet weight was revealed in ovariectomized animals. Castration markedly reduced the thickness of the vaginal wall. nNOS inhibition by 7‐NI had no impact on vaginal lubrication. Conclusions Irrespective of the hormonal status, sildenafil increased vaginal lubrication. The vaginal effect of sildenafil was independent of the nNOS pathway and more pronounced in ovariectomized animals.